Electroforming as a Novel One-Step Manufacturing Method of Structured Aluminum Foil Current Collectors for Lithium-Ion Batteries - Phillip Scherzl; Michael Kaupp; Wassima El Mofid; Timo Sörgel (Batteries, 2023)
Conventionally, cathode current collectors for lithium-ion batteries (LIB) consist of an aluminum foil generally manufactured by a rolling process. In the present work, a novel one-step manufacturing method of structured aluminum foil current collectors for lithium-ion batteries by electroforming is introduced. For this, a low-temperature chloride-based ionic liquid was used as an electrolyte and a rotating cylinder out of stainless steel as a temporary substrate. It was shown that the structure of the aluminum foils can be adjusted from dense and flat to three-dimensional by choosing an appropriate substrate rotation speed and current density. Scanning electron microscopy (SEM) and white light interferometry (WLI) were utilized to analyze the foils’ surface morphology, structure and topography. The SEM analysis of the aluminum foils showed that the rolling process produced a foil with small grains, while electrodeposition resulted in foils with different degrees of grain growth and seed formation. This was in total agreement with WLI results that revealed significant differences in terms of roughness parameters, including the peak-to-valley difference Rpv, the root-mean-square roughness Rq and the arithmetic mean roughness Ra. These were, respectively, equal to 6.8 µm, 0.35 µm and 0.279 µm for the state-of-the-art foil and up to 96.6 µm, 10.92 µm and 8.783 µm for the structured electroformed foil. Additionally, cyclic voltammetry (CV) of the aluminum foils was used to investigate their passivation behavior within the typical LIB cathode potential operation window. The strong decrease in the current density during the second cycle compared to the first cycle, where an anodic peak appeared between 4.0 and 4.4 V vs. Li/Li+, demonstrated that passivation occurs in the same manner as observed for commercial Al current collectors.